(untitled) (The Educator Journal, 2022)
Higher education is the key to the overall development of a country like Nepal, whose population is ephemeral through a demographic transition. Currently, 11 universities, four health academies and 1432 higher education institutions associated (constituent and affiliated) are providing mainstream higher education in Nepal. However, providing access to higher education to the increased number of the eligible population still remains a challenge, while on the other hand, the quality of higher education and its significance to local and national primacy has been a concern. In the meantime, planners, policymakers and researchers need timely and relevant data in order to meet the challenge faced in their relevant sectors. Despite having challenges in higher education in Nepal, Tribhuvan University, the oldest and leading university, is producing more Masters, MPhil, and PhD graduates for the nation’s overall development.